Expert Testimony on Eyewitness Evidence: In Search of Common Sense. (3rd September 2013) - Houston, Kate A.; Hope, Lorraine; Memon, Amina; Don Read, J.; Otgaar, Henry; Sauerland, Melanie; Petrila, John P.
<x xml:space="preserve">Abstract</x> Surveys on knowledge of eyewitness issues typically indicate that legal professionals and jurors alike can be insensitive to factors that are detrimental to eyewitness accuracy. One aim of the current research was to assess the extent to which judges, an under‐represented sample in the extant literature, are aware of factors that may undermine the accuracy and reliability of eyewitness evidence (Study 1). We also sought to assess the knowledge of a jury‐eligible sample of the general public (drawn from the same population as the judges) and compared responses from a multiple choice survey with a scenario‐based, response‐generation survey in order to investigate whether questionnaire format alters the accuracy of responses provided (Study 2). Overall, judges demonstrated a reasonable level of knowledge regarding general eyewitness memory issues. Further, the jury‐eligible general public respondents completing a multiple choice format survey produced more responses consistent with experts than did participants who were required to generate their own responses. The results are discussed in terms of the future training requirements for legal professionals and the ability of jurors to apply the knowledge they have to the legal context. Copyright © 2013 John Wiley & Sons, Ltd.